1998
DOI: 10.1097/00003246-199808000-00038
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling short-term central venous catheters to prevent catheter-related infection

Abstract: Tunneling decreases central venous catheter-related infections. However, current evidence does not support routine tunneling until its efficacy is evaluated at different placement sites and relative to other interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(45 citation statements)
references
References 25 publications
1
41
1
2
Order By: Relevance
“…al (17) . Many randomized clinical trials and reviews have clearly demonstrated that the use of tunneled catheters and those with cuffs reduce the risks of catheter-related sepsis by 44% -77% as compared to the use of non-tunneled catheters and those without cuff, by reducing the risks of bacterial migration from the skin to the circulation and diminishing the formation of biofilm (6,8,13,23) . There was no statistically significant difference in regard to the use of Mupirocin versus honey for bacteremias caused by S. aureus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…al (17) . Many randomized clinical trials and reviews have clearly demonstrated that the use of tunneled catheters and those with cuffs reduce the risks of catheter-related sepsis by 44% -77% as compared to the use of non-tunneled catheters and those without cuff, by reducing the risks of bacterial migration from the skin to the circulation and diminishing the formation of biofilm (6,8,13,23) . There was no statistically significant difference in regard to the use of Mupirocin versus honey for bacteremias caused by S. aureus.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CVCs should be quite limited due to the frequent occurrence of bloodstream infection; as shown in several studies, the rate is approximately 40% (1)(2)(3)(4)(5)(6)(7) . Infection is the second leading cause of mortality among patients with end stage renal disease (ESRD) and represents, approximately, 14% of deaths among these individuals, preceded only by cardiovascular events (8) .…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from studies on tunneling effi cacy have suggested that this technique reduces CVC infections in patients with short-term devices, where most colonized pathogens arise from the catheter insertion site. A meta-analysis of randomized controlled trials demonstrated that tunneling decreased catheter colonization by 39% and bloodstream infection by 44% compared to non-tunneling [36]. Th ese results were partly due to one trial with CVCs inserted via the internal jugular vein, and no signifi cant risk reduction was observed when only the data from fi ve subclavian catheter trials were pooled.…”
Section: Tunnelingmentioning
confidence: 99%
“…Catheter-related infections were defined according to standard guidelines (9,28,29). Catheter-associated bacteremia was defined as either (1) a single positive blood culture together with a positive culture of the catheter tip or exit site with an identical organism or (2) two or more positive blood cultures (or a single positive blood culture for S. aureus) with no evidence of infection source other than the device.…”
Section: Definitionsmentioning
confidence: 99%